Exercise-related goals and motives of persons with Multiple Sclerosis in a German Cohort - Streber, René; Geidl, Wolfgang; Tallner, Alexander; Pfeifer, Klaus (Rehabilitation in multiple sclerosis (RIMS), 2015)
Background In contrast to the many positive health effects of physical activity (PA), physical inactivity is common among persons with Multiple Sclerosis (pwMS). Few studies focused on an individual’s motives and goals of exercise participation in that population. Psychometric properties of the german Berner Motiv- und Zielinventar (BMZI) that was primarily designed for adults without chronic diseases as well as motives and goals of sport participation in pwMS were analyzed. Methods Motives and goals were assessed with the BMZI in an online-based survey in Germany (n=1100). It includes 28 items that are rated from 1 - “not at all true for me” to 5 - “very true for me” and covers eight motives. Psychometric properties were analyzed with an exploratory (EFA) and confirmatory factor analysis (CFA). Additionally, the open question for significant other goals and motives that were not covered in the BMZI were analyzed with a qualitative content analysis. Results Health (M=4.0; SD=0.9) and fitness (M=4.1; SD=0.9) are the most significant motives, whereas sociability (MW = 2.2; SD = 1.0) and competition (M = 1.8; SD = 1.0) play a subordinate role. EFA revealed a six-factor structure. CFA provided evidence of an acceptable model fit (e.g. GFI=0.825, RMSEA=0.076). Content analysis revealed several further themes that are more disease-specific. Discussion The BMZI seems to be a reliable and valid instrument to measure multi-dimensional motive profiles in pwMS but potentials for further development for that specific population were identified. Additionally, this work provides the first insight into the exercise-related motives and goals profiles of pwMS in Germany. In combination with other functional and psychological characteristics, the consideration of a person’s exercise-related motives and goals might be helpful designing person-oriented PA promotion strategies.
Keywords: physical activity; exercise; motives; goals; motivation; multiple sclerosis